2020
DOI: 10.1108/ijopm-05-2019-0395
|View full text |Cite
|
Sign up to set email alerts
|

Maximising “Community Benefits” in public procurement: tensions and trade-offs

Abstract: PurposeThis study aims to illuminate the challenges involved in implementing community benefits (CBs), a sustainable public procurement policy that ensures that there are positive social and economic outcomes for the local community when public money is spent on goods, works and services.Design/methodology/approachInterviews and focus groups were conducted with public sector buyers and suppliers in Wales with experience in implementing CBs. Resource dependence theory was used to examine the extent to which dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 65 publications
1
39
0
1
Order By: Relevance
“…Although coming from different directions, the empirical and theoretical work of the selected papers for this special issue point out that unintended outcomes may arise when relevant interactions are disregarded. Overall, these studies indicate the reasons why they may vary between ignorance and self-interest (Nath et al, 2020;Silvestre et al, 2020;Glover, 2020) or, due to complexity, these interactions may be difficult to identify (Carter et al, 2020;Wontner et al, 2020;Ye et al, 2020). While these studies significantly contribute to describing the phenomena of trade-offs and unintended issues, it is still not clear how such problems emerge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although coming from different directions, the empirical and theoretical work of the selected papers for this special issue point out that unintended outcomes may arise when relevant interactions are disregarded. Overall, these studies indicate the reasons why they may vary between ignorance and self-interest (Nath et al, 2020;Silvestre et al, 2020;Glover, 2020) or, due to complexity, these interactions may be difficult to identify (Carter et al, 2020;Wontner et al, 2020;Ye et al, 2020). While these studies significantly contribute to describing the phenomena of trade-offs and unintended issues, it is still not clear how such problems emerge.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Wontner et al (2020) explores the challenges of implementing a sustainable public procurement policy in the form of community benefits to ensure that public expenditures result in positive social and economic outcomes for the local community. Drawing on resource dependence theory, they found that while implementing community benefit policies improve economic and social outcomes, differing views between buyers and suppliers often creates tensions, while unintended consequences may result when one form of community benefits (CB) is promoted over another.…”
Section: Overview Of Papers In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…They found that increasing public purchases helped to raise the investment of vendor firms. Wontner et al (2020) found that implementing community benefit in the procurement process and policy would increase public projects' economic and social outcomes. However, potential differences in the comparison of community benefit and views of buyers and sellers could be constraints in the way of procurement.…”
Section: International Contextmentioning
confidence: 99%
“…In relation to the barriers that currently hold back social procurement, one of them is the difficulty to establish objectives for the quantification of the social value [37]. Wonter et al [38], in their study on community benefits in Welsh public procurement, pointed out how suppliers show their rejection with the introduction of socio-economic criteria in the tendering process, since these costs end up being passed on to the final customers or absorbed by the companies, and this entails a risk of exclusion of small and medium enterprises in public procurement. The barriers to the introduction of social criteria in public procurement could be one of the future research lines for scientific academics.…”
Section: Literature Reviewmentioning
confidence: 99%